Double Autosomal Aneuploidy: A Case of Trisomy 18 and 21 Mosaicism in A Neonate with Clinical Down Syndrome - Aliyyah Mohammad Khuzaini; Adilah W. Ab Rahim; Lim Yee Shan; Foong Eva; Halimah Abdul Halim (Malaysian Paediatric Association, 2024)
Indexed by ERA